Formulation and Evaluation of Oral Mucoadhesive Microspheres of Ofloxacin for Peptic Ulcer Use - Deshmukh, Rohitas; Harwansh, Ranjit K.; Prajapati, Mahendra; Sharma, Bhavana (Trends in Sciences, 2023)
A peptic ulcer is a disease that affects the stomach lining caused by Helicobacter pylori. The present research aimed to formulate and evaluate the mucoadhesive microsphere of ofloxacin for the effective and safe treatment of peptic ulcers. The mucoadhesive microspheres were developed using natural polymers like Guar gum, Sodium alginate, and Chitosan using the emulsification cross-linking method. A total of 8 batch formulations were prepared using 23 full factorial designs. The prepared microspheres were evaluated various parameters such as % yield, entrapment efficiency, drug release study, in vitro wash-off test, optimization was done by the design of expert which was further subjected to statistical analysis that was kinetic release mechanism, compatibility studies were performed such as FTIR and DSC. Using factorial design 23 for the maximum possible formulation, the optimized formulation was found to be F5 in terms of better release for a longer time and with better mucoadhesive properties on the use of guar gum, sodium alginate, and chitosan in ratio 1:1:2. Second-order polynomial equations were derived for absorbing responses after the application of ANOVA, after omitting the non-significant (p ≥ 0.05) coefficients. %CDR 56.10 % for an extended period of 8 h, % EE exhibited 86.25±1.16. The sustained release activity of F5 might be due to the adhesion of the polymer to the gastric mucosa for more extended periods of 71 % to 8 h. it is also favoured by the suitable particle size of the optimized formulation. The result indicated that the prepared mucoadhesive microspheres can release the ofloxacin in sustained manner and helps in the management of peptic ulcer. HIGHLIGHTS Ofloxacin loaded mucoadhesive microsphere was prepared for treatment of peptic ulcer The mucoadhesive microspheres were developed using natural polymers A total of 8 batch formulations were prepared using 23 full factorial designs Drug release from the optimized microsphere was 71 % to 8 h The developed microsphere can effectively deliver the drug in stomach part GRAPHICAL ABSTRACT